Comment on the advisory opinion of the International Court of Justice on the legality of the threat to use nuclear weapons in 1996 - Ibrahim, Esam Elden Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
The International Court of Justice had the opportunity to establish the principles of international humanitarian law and restrict the use or threat of nuclear weapons, on the occasion of its fatwa, on the legality of the threat or use of nuclear weapons at the request of the United Nations General Assembly, after realizing that the continued development of nuclear weapons exposes humanity to great risks, and its request It states, "Is the threat or use of nuclear weapons in any circumstance permissible under the rules of international law" (Atalm, 1996), (Shahab, 2000), Therefore, the comment seeks to answer the question: What is the legality of possession, production and development of nuclear weapons? What is the extent of the legality of the threat to use it in light of the advisory opinion of the International Court of Justice in this regard? Was the decision of the International Court of Justice in favor of documenting the principles of international humanitarian law and international human rights law? Or was it biased in its decision to the interests of a particular class itself?The researcher used in that descriptive, descriptive and critical analytical method, and the results that lead to criticism of the work of the International Court of Justice in this regard were reached on the premise that they tended towards tipping the political nature of the issue presented to it under the pressures and directions of the major nuclear states and this strengthens my criticism to the United Nations that I see It only works for the benefit of the major powers under the auspices of the Security Council by veto (right to veto) at a time when the Security Council itself is responsible for maintaining international peace and security, just as it can be said that the United Nations does not work for the benefit of mankind but works for the five major countries Even with regard to nuclear weapons Regardless of whether or not there was a threat to international peace and security.From this standpoint, the researcher reached several recommendations, the most important of which is the necessity of the independence of the International Court of Justice in its work from the political considerations of member states, especially the major countries, as a step to establish and support international peace and security in a practical way in practice. The United Nations should also reconsider what is known as a veto, which is and it is rightly one of the most important and most important measures that truly threaten international peace and security.
Keywords: International Court of Justice; Nuclear Weapons; United Nations